Peran Perangkat Desa dalam Akuntabilitas Pengelolaan Dana Desa: Studi Kasus Desa Raharja Kecamatan Wonosari Kabupaten Boalemo Provinsi Gorontalo - Siskawati Nur; Siti Pratiwi Husain; Lukman Pakaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the role of Raharja Village apparatus in accountability of village fund management. The data in this study uses a descriptive qualitative method. Data sources were obtained from the observation, interview and documentation stages. Based on this study, it can be concluded that the role of village apparatus in accountability of village fund management in Raharja Village, Wonosari District, Boalemo Regency in 2024 as a whole can be considered to have run well. This is proven by the village apparatus who have carried out their duties in managing village funds well. However, there are several tasks that are carried out by other village officials due to a lack of understanding in the village officials concerned. Such as in the preparation of expenditure transaction reports that should be carried out by the treasurer, but are instead carried out by the secretary. Therefore, it is necessary to improve the quality of knowledge and skills of village officials to support their performance in running the village government.